LITERATURE OF REVIEW THE INFLUENCE OF EVENT STRATEGY, CUSTOMER LOYALTY AND PRODUCT ON PURCHASE DECISIONS FOR THE LOONY FASHION BRAND - Elna Rosdiana Putri (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
This research focuses on a literature review thatexamines the influence of event strategy, customerloyalty and product on purchase decisions. Thisresearch examines Loony Fashion Brand products.The research was designed using a quantitativeapproach with the population of visitors who hadused the brand at Bazaar Mall Grand Galaxy Park. Theresults of the data and information collected will thenbe processed for feasibility and hypotheses usingSPSS 25 statistical tools.